Trente ans d’images dans Mappemonde - Clarisse Didelon-Loiseau; Hervé Théry (M@ppemonde)
To celebrate 30 years of publication, Mappemonde has thoroughly analysed both its paper and electronic archives in order to constitute a database referencing and describing all the images published since 1986. This analysis traces the review’s formal transformation as it became institutionalized, summarizes how the role of images has evolved in geography, and measures the impact of technical and methodological progress. It also uncovers trends within the discipline in terms of spaces or themes covered.